The Diamond Jenness collections from Bering Strait - Morrison, David A. (Mercury series., 1991)
This study examines the Bering Strait collections made by Diamond Jenness in 1926 at Cape Prince of Wales and Little Diomede Island in Alaska. These collections, not previously described, constitute the first systematic archaological work in Alaska and resulted in the identification of Old Bering Sea culture and the stratigraphic position of Thule culture.